HYDRAZIDE OF o-HYDROXYBENZOIC ACID AND ITS ERIVATIVES. SYNTHESIS AND PROPERTIES - Nurkenov O.A.; Fazylov S.D.; Zhurinov M.Zh.; Satpaeva Zh.B.; Burkeev M.Zh.; Seilkhanov T.M.; Satybaldin E.D. (Scientific Journal of Pedagogy and Economics, 2020)
The article presents the results of a study by the authors of the article on the development of new ways of synthesis and study of the biological activity of hydrazide derivatives of o-hydroxybenzoic acid. Methods for the preparation of hydrazone, oxadiazole, thiosemicarbazide, 1,2,4-triazole-3-thionic derivatives and methods for their further modification are described. The condensation reaction of hydroxybenzoic acid hydrazides with 1-deoxy2,3,4,6-tetra-O-acetyl-D-glucopyranosyl isothiocyanate synthesized their corresponding acetylated glycosyl-containing thiosemicarbazide derivatives. The structures of the synthesized compounds were studied by 1 H and 13C NMR spectroscopy, as well as by the data of two-dimensional spectra of COSY (1 H-1 H) and HMQC (1 H-13C). The values of chemical shifts, multiplicity, and integrated intensity of 1H and 13C signals in one-dimensional NMR spectra were determined. Using spectra in the formats COSY (1 Н-1 Н) and HMQC (1 Н-13С), homo- and heteronuclear interactions were established, confirming the structure of the compounds under study. The results of evaluating their antimicrobial, anti-inflammatory and cytotoxic activity (in vitro) on cultures of human monocytic cell lines MonoMac-6 and THP1Blue are described.